Healthy Mondays or Sundays? Weekday Preferences for Healthy Eating and Cooking among a Food Insecure Population in a U.S. Urban Environment. Issue 1 (2nd January 2022) - Ali, Shahmir H.; Gu, Yuxuan; Yan, Sally; Craig, Hope C.; Adams, Lindsay; Poirier, Lisa; Park, Reuben; Gunen, Bengucan; Gittelsohn, Joel
ABSTRACT: Food insecure populations are in need of targeted nutritional interventions and understanding their food behaviors can inform effective weekday-based health campaigns. We examine weekday preference in healthy eating, cooking, and cooking with children among food pantry clients in Baltimore City. A cross-sectional survey of 74 food pantry clients was conducted on weekday-based preferences of these behaviors. Compared to Monday, clients were more likely to eat healthy on Friday ( p = .04), Thursday ( p = .04), and Saturday ( p = .002), and more likely to cook on Sunday ( p = .002). Future interventions should consider weekday preferences in nutrition campaigns (nutrition knowledge, food skills) among food insecure populations.